Image processing and its potential application in companies with digital strategy - Taquía-Gutiérrez, José Antonio (2017)
Peruvian retail market today, more than ever, has turned the phrase “everything goes through the eyes” into a competitive tool. The design and optimization of space, as well as visual merchandising, are techniques that impact the sale new concepts such as omnicanality and buying experience are fed by data analytics in order to describe the commercial mode; and new qualitative sources of information, among them color theory, specially help to understand and predict the impact of future decisions on the point of sale. This paper describes the utility of image processing techniques to innovate the retail market in the effort to extract useful information from advertising pieces frequently used in this sector.